Suicidal events among pathological gamblers: The role of comorbidity of axis I and axis II disorders. Issue 3 (28th February 2015) - Bischof, Anja; Meyer, Christian; Bischof, Gallus; John, Ulrich; Wurst, Friedrich Martin; Thon, Natasha; Lucht, Michael; Grabe, Hans Joergen; Rumpf, Hans-Juergen
Abstract: The risk for suicidal ideation and suicide attempts among pathological gamblers is high compared to the general population. Little is known about the interplay of Axis I and Axis II disorders, severity of gambling disorder, and suicidal ideation and suicide attempts. The study aims to address this linkage. The sampling design of the study "Pathological Gambling and Epidemiology" (PAGE) included four recruitment channels: general population, gambling locations, project telephone hotline, and in-patient treatment for pathological gambling. A total of 442 study participants with lifetime pathological gambling received a clinical interview. The multivariate analysis showed mood disorders (Relative Risk Ratio, RRR=5.14, 95%-Confidence Interval, CI=2.91–9.07), substance use disorders (RRR=1.73, CI=1.02–2.94), and early onset of gambling disorder (RRR=0.96, CI=0.93–0.99) to be associated with suicidal ideation. Suicidal attempts were associated with female sex (RRR=3.58, CI=1.56–8.19), mood disorders (RRR=11.92, CI=4.70–30.26), and Cluster B personality disorders (RRR=2.40, CI=1.13–5.10). Among study participants with suicide attempts, more had a Cluster B personality disorder than among participants with ideation solely (RRR=3.08, CI=1.48–6.40). Among this large mixed sample of pathological gamblers, high proportions of individuals with suicidal events, multi-morbidity on Axis I, and a strong linkage to Cluster B personality disorders were found. Highlights: Cluster B personality disorders are a serious risk factor for suicide attempts in pathological gamblers. Increased rates of suicidal events among pathological gamblers indicated a need for early detection and intervention. Mood disorders are the most important risk factor for suicidal events in individuals with gambling disorders.